Free Breathing Abdominal Imaging with Fat-Water Separation Using 3D Radial Stack-of-Stars Trajectory - Riad S. Ababneh (Jordan Journal of Physics, 2025)
In earlier studies of fat-water separation using dynamic imaging applications, the three-dimensional (3D) MRI failed to provide high spatial and temporal resolution. This work proposes a fat-water separation strategy in the abdomen during free breathing using the 3D stack-of-stars (SOS) radial sampling technique. Radial trajectories are less sensitive to motion and have a higher sampling density for the central k-space, allowing for better performance in capturing dynamic information. To this end, a 3D radial TrueFISP sequence was modified to enable the echo time TE to change from projection to projection, where all z-phase encoding was acquired at a single projection angle before switching to the next projection angle. As a result, the fat signal is forced to behave in a specific and easily recognizable fashion over time. Using temporal processing, temporal variations imposed on fat signals can be recognized and fat signals can be separated from water signals. Keywords: Fat-water separation, TrueFISP, Stack-of-stars, Free breathing.